Tingkat Kecemasan Remaja Putri yang Mengalami Masa Pubertas di SMP Negeri 1 Selorejo Kabupaten Blitar - Fenika Aulia Permatasari Saputri (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2016)
The anxiety occurred in adolescents one of whom are the result of physical changes. Besides, emotional and social chages also affected the psychology of adolescents who experience puberty. The purposeof this study was to determine the level of anxiety of young women who experience puberty at SMPN 1 selorejo district Blitar. Method: the research method used descriptive design. The entire population was female students (early teens) VII grade in SMP Negeri 1 Selorejo Blitar in accordance with the inclusion criteria 53 students.The sample was 53 students used purposive sampling technique. The data collection used the instruments of the Zung Self-Rating Anxiety Scale (SAS/SARS) modified researchers to support this research. The data was taken on 13 April 2015. Changes at puberty of adolescent girls were menstruating on early age of 12 years in category of mild anxiety. Recommendations from this study were expected that the school was able to maintain a state of anxiety with the effectiveness of UKS and other facilities for adolescent girls to exchange opinions in order to reduce the anxiety and able to cope with mild anxiety from getting to a higher level